2012
DOI: 10.1016/j.bone.2011.07.016
|View full text |Cite
|
Sign up to set email alerts
|

High abundance of CD271+ multipotential stromal cells (MSCs) in intramedullary cavities of long bones

Abstract: Aspiration of iliac crest bone marrow (ICBM) remains the most frequent technique used in harvesting multipotential stromal cells (MSCs) for bone regeneration. Although this tissue type is easily accessed by a surgeon, it has a low frequency of MSCs, which is significant given the high cell numbers required for bone regeneration strategies. Lipoaspirates possess higher MSC frequencies, albeit cells with a differentiation profile less suited to orthopaedic interventions. Intra-medullary cavities of long bones ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 61 publications
5
46
1
Order By: Relevance
“…3b, CD271 + cells derived from both IC BM aspirate and RIA fluid were positive for classical MSC markers CD73 and CD90 (Dominici et al, 2006;VeyratMasson et al, 2007). The expression of CD105, another well-known MSC marker (Barry et al, 1999;Pittenger et al, 1999) was slightly lower compared to CD73 and CD90, as described previously (Martinez et al, 2007;Cox et al, 2012), but remained highly specific for CD271 + cells. Consistent with their non-haematopoietic nature, CD271 + cells from both sources did not express markers for haematopoietic progenitors (CD34), megakaryocytes/ platelets (CD61), B-cells (CD19), endothelial cells (CD31) and myeloid cells (CD33).…”
Section: Molecular Profile Of Mscssupporting
confidence: 63%
See 4 more Smart Citations
“…3b, CD271 + cells derived from both IC BM aspirate and RIA fluid were positive for classical MSC markers CD73 and CD90 (Dominici et al, 2006;VeyratMasson et al, 2007). The expression of CD105, another well-known MSC marker (Barry et al, 1999;Pittenger et al, 1999) was slightly lower compared to CD73 and CD90, as described previously (Martinez et al, 2007;Cox et al, 2012), but remained highly specific for CD271 + cells. Consistent with their non-haematopoietic nature, CD271 + cells from both sources did not express markers for haematopoietic progenitors (CD34), megakaryocytes/ platelets (CD61), B-cells (CD19), endothelial cells (CD31) and myeloid cells (CD33).…”
Section: Molecular Profile Of Mscssupporting
confidence: 63%
“…In other words, the presence of MSCs is inferred by analysing their progeny whereas their native characteristics remain unknown. We were the first group to use the CD271 + phenotype to characterise native MSCs in the IC BM (Jones et al, 2002; and in long bones (Cox et al, 2012), later confirmed independently (Buhring et al, 2007;Kuci et al, 2011;Tormin et al, 2011;Maijenburg et al, 2012;Rasini et al, 2013 …”
Section: Introductionmentioning
confidence: 70%
See 3 more Smart Citations